On the fate of the Anthropocene-geomorphological evolution of the Outer Dieng Highland (Indonesia) under massive anthropogenic acceleration - Grace Helena Amaranthois Kapisan; Arif Ashari; Xingzhou Jiang; Sumayyah Aimi Mohd Najib; M.S. Roganda; Yusuf Susena; Afrinia Lisditya Permatasari; Anggoro Putranto; Edi Widodo; Bagus Tegar Sakti Prakosa; Raisya Arzety Olivia; Heng Zhang (Universitas Negeri Yogyakarta, 2026)
The Great Acceleration since the mid-20th century, resulting from the dominance of anthropogenic activities on Earth, has had a significant impact on the environment, including geomorphological evolution. This paper aims to investigate the Anthropocene-geomorphological evolution in the outer Dieng Highlands, shaped by massive anthropogenic acceleration. This study employs a geomorphological approach. Data were collected through observation, remote sensing image interpretation, literature, and documents. The data were analyzed using descriptive geomorphological analysis, supported by geographic information systems and remote sensing. There are two significant findings in this study. First, anthropogenic activities during the Anthropocene have been highly dominant, marked by extensive land use for agriculture and settlements over the past five decades. Second, the Outer Dieng Highland is a volcanic complex; however, its current geomorphological evolution is primarily driven by the acceleration of exogenic processes induced by anthropogenic activities. Erosion and mass movements occur on a large scale, increasing drainage density, particularly in older volcanic units and less-resistant materials. In sum, this study offers new insights into the impact of anthropogenic activities on the acceleration of exogenic destruction across various structures within the volcanic complex.